Designing a transboundary multistakeholder platform in the Incomati: Learning from other African basins - Thwala, Setsabile; Nehring, Ryan; Lautze, Jonathan F. (CGIAR, 2024)
A workshop organized by IWMI and IFPRI enabled stakeholders in Mozambique to learn lessons from other shared-basin management structures across Africa